The efficacy of valproate in acute mania, bipolar depression and maintenance therapy for bipolar disorder: an overview of systematic reviews with meta-analyses - Flávio Kapczinski; Jair Mari; Luiz Henrique Junqueira Dieckmann; Daniel Prates-Baldez; Michel Haddad; Naielly Rodrigues da Silva (BMJ Open)
Objective This study aims to conduct an overview on the comparative efficacy of valproate in acute mania, bipolar depression and maintenance treatment of bipolar disorder (BD).Method We performed an overview of systematic reviews with meta-analyses of randomised controlled trials (RCTs), registered in PROSPERO (CRD42024497749). We searched Medline and Cochrane Database of Systematic Reviews. Summary measures comparing valproate with placebo or other active drugs were described.Results We included 26 systematic reviews. For acute mania (31 RCTs, n=4376), valproate showed a significantly better response than placebo in two high-quality systematic reviews (RR=1.42; 95% CI: 1.19 to 1.71) (OR=2.05; 95% CI: 1.32 to 3.20). No significant differences with lithium were found in most outcomes. Valproate had similar efficacy to quetiapine and lower efficacy compared with risperidone, with conflicting results when compared with olanzapine. In bipolar depression (7 RCTs, n=399), valproate was more effective than placebo in reducing depressive symptoms (OR=2.80; 95% CI: 1.26 to 6.18) and achieving remission (OR=2.4; 95% CI: 1.09 to 5.29) (OR=2.15; 95% CI: 0.82 to 5.6), considering the results of three high-quality systematic reviews. No significant difference was observed with lithium, lurasidone, quetiapine or olanzapine plus fluoxetine, but valproate showed superior efficacy to aripiprazole, ziprasidone and agomelatine. In maintenance treatment (11 RCTs, n=1063), valproate was superior to placebo in preventing relapse of any mood episode in two high-quality systematic reviews (RR=0.63; 95% CI: 0.48 to 0.83) (RR=0.63; 95% CI: 0.47 to 0.83). No significant difference was found with lithium, olanzapine or lamotrigine.Conclusion This overview highlights favourable results for valproate compared with placebo in all phases of BD, as well as presenting specific results in comparison with other active drugs. However, these results must be interpreted considering the methodological limitations of our study.